2022
DOI: 10.3390/genes13081329
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and MicroRNA-Target Variants Associated with Autism Spectrum Disorder and Related Disorders

Abstract: Autism spectrum disorder (ASD) is a childhood neurodevelopmental disorder with a complex and heterogeneous genetic etiology. MicroRNA (miRNA), a class of small non-coding RNAs, could regulate ASD risk genes post-transcriptionally and affect broad molecular pathways related to ASD and associated disorders. Using whole-genome sequencing, we analyzed 272 samples in 73 families in the New Jersey Language and Autism Genetics Study (NJLAGS) cohort. Families with at least one ASD patient were recruited and were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The GO enrichment and PPI network analyses pointed to several biological processes that are important for ASD etiology, such as neuronal development and histone modification. Several of the terms (e.g., "histone modification", "actin binding") also showed enrichment in the cohort in our previous studies of SNVs [32,46]. These genes are strong candidates for future study of their contribution to ASD.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The GO enrichment and PPI network analyses pointed to several biological processes that are important for ASD etiology, such as neuronal development and histone modification. Several of the terms (e.g., "histone modification", "actin binding") also showed enrichment in the cohort in our previous studies of SNVs [32,46]. These genes are strong candidates for future study of their contribution to ASD.…”
Section: Discussionmentioning
confidence: 65%
“…Lastly, we limited our analysis to interactions among SVs. Several types of data, including coding SNVs, and microRNA variants have been identified in the NJLAGS cohort [32,46]. Integrative analysis of candidate genes from multiple types of variants could further improve the power of the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested the role of miRNAs in the development of autism. Wong et al [ 62 ] identified variants in five brain-expressed miRNAs, which target 326 genes, and 3′ UTR miRNA target regions of 152 genes potentially involved in neurodevelopmental disorders, including autism. miRNA could post-transcriptionally regulate autism-related risk genes and affect various molecular pathways related to autism and associated disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding de novo mutations in chromatin interactions were found to alter the expression of target genes at early neurodevelopmental stages ( 30 ). Another study identified miRNA and miRNA targeting variants associated with ASD and related disorders ( 31 ). Inflammatory mechanisms and vitamin D are also reported to play an important role in the pathophysiology of ASD, and 25-OH-vitamin D levels in ASD patients were significantly negatively correlated with c-reactive protein, neutrophil-lymphocyte ratio, and neutrophil counts.…”
Section: Discussionmentioning
confidence: 99%